Humbness Conditions of Polymer Mixtures - Jafarov, V.J.; Manafov, M.A.; Alkhanov, P.S.; Khalilova, S.M.; Rajabova, M.C. (Herald of Azerbaijan Engineering Academy, 2023)
Explaing the importance of creating polymer blends. Easy PE-PP mix selected by comparative analysis of adopted systems determined to be more effective as a result of numbness and the possibility of purchasing new high-quality materials and areas of use was revealed.